Effect of marketing public relations strategies on Chocodot sales growth on Shopee - Nurhadi, Zikri Fachrul; Sorgania, Nissa Septiani; Sahharon, Hamizah (PRofesi Humas, 2026)
Background: While Chocodot possesses a strong brand identity as a signature souvenir from Garut, empirical evidence regarding the effectiveness of its Marketing Public Relations (MPR) strategy in driving sales on Shopee remains limited. This study aims to address this gap by analyzing the extent to which Chocodot’s Marketing Public Relations activities influence sales growth on the Shopee platform. Purpose: This study aims to test how much influence public relations marketing strategies have on increasing Chocodot sales on the Shopee platform. Methods: This study used an exploratory quantitative approach, with a sample of 35 Shopee user respondents in Garut selected using a non-probability sampling method. Data were collected using a questionnaire with validity and reliability tests. Results: The results indicate that Chocodot’s marketing public relations strategy, which consists of image building, sales support, and public opinion management, is in the moderate category with an average score of 3.57. Statistical analysis shows that the Marketing Public Relations strategy has a positive and significant influence on increasing sales by 78.3% (R² = 0.783). This study found that the level of customer loyalty for routine purchases can still be improved because consumer shopping habits are still dominated by situational needs. Conclusion: This study concludes that an integrated Marketing Public Relations strategy and consistent service quality are important for building customer loyalty in the digital environment. Implications: For Chocodot management, the results of this study can be the basis for designing more effective communication strategies to increase sales through strengthening publicity, consumer engagement, and maintaining reputation in the market.